Intrahepatic activated leukocyte cell adhesion molecule induces CD6highCD4+ T cell infiltration in autoimmune hepatitis - Qian, Qiwei; Cui, Nana; Huang, Bingyuan; Zhao, Yudong; Liu, Qiaoyan; Hu, Mingli; Li, Bo; Wang, Qixia; Miao, Qi; You, Zhengrui; Ma, Xiong; Tang, Ruqi (Frontiers in Immunology, 2022)
Background and objectives: Autoimmune hepatitis (AIH) is characterized by the expansion and accumulation of pathogenic T cells in liver. Although CD6 and its ligand activated leukocyte cell adhesion molecule (ALCAM) are involved in the evolution of multiple inflammatory diseases, their roles in the pathogenesis of AIH remain unknown. Herein, we aimed to investigate ALCAM-CD6 axis in AIH development. Methods: Immunohistochemistry was performed to examine hepatic expression of CD6 and ALCAM. The concentration of serum ALCAM was evaluated by ELISA. The phenotypes of liver infiltrating T cells were determined by flow cytometry. Primary human CD4+ T cells were used for functional studies. Results: Our data showed that patients with AIH exhibited significantly higher expression of CD6 in the liver as compared to primary biliary cholangitis (PBC), chronic hepatitis B (CHB), non-alcoholic liver disease (NAFLD), and healthy controls (HC). In addition, hepatic CD6 expression was strongly correlated with disease severity of AIH. CD6 was mainly expressed on CD4+ T cells in the liver and intrahepatic CD6highCD4+ T cells demonstrated stronger proinflammatory response and proliferation features than CD6low counterparts in both AIH and HC. ALCAM, the ligand of CD6, was highly expressed in the hepatocytes of AIH and serum ALCAM was strongly associated with clinical indices of AIH. Interestingly, close spatial location between CD6+CD4+ T cells and ALCAM+ hepatocytes was observed. Finally, we found that CD6highCD4+ T cells showed enhanced capacity of trans-endothelial migration in vitro, which could be promoted by recombinant ALCAM. Conclusions: Our study found that ALCAM-CD6 axis was upregulated in the AIH liver, suggesting a potential target for alleviating AIH.